The factor associated with occurrence of mastitis caused by Staphylococcus aureus - Tobinaga, T.; Yamamoto, H.; Makita, K. (2012)
[Purpose] Mastitis is a very important disease in dairy farming. In Ohotsuku, Japan, Staphylococcus aureus (SA) mastitis incidence increased after the introduction of anonymous post-dipping Iodine-based product A. The purpose of this study was to examine the association between the product A and the disease increase. [Materials and methods] The dairy cows monitoring data for 5 farms using product A and 4 farms using another anonymous Iodine-based product B in the dairy farms which belong to Ohotsuku Farmers’ Association and encountered with SA mastitis incidence were used for this analysis. Farming style (tie or free stall), pre-milking teat disinfectant (2 products) and post-dipping products were selected as explanatory variables. The incidence of SA mastitis on each teat between April 2005 and March 2007 was selected as a response variable. In univariate analysis, Generalized Linear Models (GLMs) with Poisson errors were used for the explanatory variables. In multivariable analysis, as the incidence of SA mastitis on each teat could be affected by the intra-class correlation at two levels: animal and farm levels, robust variance using Generalized Estimating Equations (GEE) was performed in statistical software R 2.13.1. The explanatory variables with the p-values less than 0.2 in the univariate analyses were selected for GEE and step-wise model simplification was performed. [Results] In univariate analysis, there was no significant difference in mean SA mastitis annual incidence per teat between tie (0.025) and free stall (0.028, p=0.53) or between two pre-dipping products (0.022 and 0.029, p=0.08). However, the mean annual incidence was significantly higher in teats which post-dipping product A was used (0.035) than those which product B was used (0.015, p<0.001). In multivariable analysis, only the use of post-dipping product A was significantly associated with the annual incidence (p<0.001). [Discussion] In the present study, only the post-dipping product was associated with the SA mastitis incidence among farming style, pre and post dipping products. Change of post-dipping product and economic evaluation after the intervention would be recommended to the farms with increased incidence.